(untitled) (Research, Society and Development, 2022)
Toxoplasmosis, caused by the protozoan Toxoplasma gondii, is considered a public health problem, causing serious consequences in immunocompromised individuals and pregnant women with acute infection, especially on the health of the fetus. Thus, the specific examination in prenatal care is indispensable from the preventive point of view. The study aimed to identify the profile of anti-Toxoplasma gondii antibodies in pregnant women followed up in prenatal care, in the period from January 2014 to January 2019, attended in the six Family Health Units (FHU), Municipality of Santa Terezinha-PE. A descriptive observational study of the case series type was conducted through the review of 583 medical records, with collection of information regarding serological research for toxoplasmosis (IgG and IgM). Of the 583 pregnant women 15/583 (2.6%) did not perform routine prenatal serology for IgM antibodies, 565/583 (96.9%) were negative and 3/583 (0.5%) were positive. For IgG antibody testing, 48/583 (8.2%) pregnant women were positive, 429/583 (73.6%) were negative, and 106/583 (18.2%) did not perform the test. When the exam was repeated during the gestational stages, 248/583 (42.5%) pregnant women had a new exam. The major problem is related to the high proportion of susceptibility of pregnant women, and the deficiency in receiving the results of both immunoglobulins favors the underreporting of cases of susceptible pregnant women. Thus, information about prophylaxis should be reinforced and the serological profile of pregnant women in the region should be monitored in order to obtain an early diagnosis, avoiding complications to the pregnant woman and the fetus.